Acquisitions versus entry: The evolution of concentration - Zava Aydemir; Armin Schmutzler (University of Zurich, Socioeconomic Institute, 2002)
We consider market dynamics in a reduced form model. In the simplest version, there are two investors and several small noninvesting firms. In each period, one investor can acquire a small firm, the other investor decides about market entry. After that all firms play an oligopoly game. We derive conditions under which increasing market concentration arises with myopic firms, we show that a model with forward-looking firms and with arbitrary numbers of investors yield similar results. We apply the framework to a Cournot model with cost synergies and a Bertrand model where acquisitions extend the product spectrum of a firm.
Keywords: D43; L11; L12; L13; 330; acquisitions; entry; concentration; synergies; product variety